2021
DOI: 10.1007/s10272-021-0963-z
|View full text |Cite
|
Sign up to set email alerts
|

The European Green Deal — More Than Climate Neutrality

Abstract: The European Green Deal aims at climate neutrality for Europe by 2050, implying a significant acceleration of emission reductions. To gain the necessary support, it needs to reduce regional and social inequalities in Europe. We present objectives in terms of jobs, growth and price stability to complement the emission reduction targets and sketch a proof-of-concept investment profile for reaching these goals. Substantial additional annual public investments, of about 1.8% of pre-COVID-19 GDP, are proposed for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(85 citation statements)
references
References 19 publications
0
64
0
Order By: Relevance
“…Over the last few decades, the notion of air pollution has become a significant subject of the public debate [145,146]. It comes as a result of growing environmental issues caused by extensive economic development.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last few decades, the notion of air pollution has become a significant subject of the public debate [145,146]. It comes as a result of growing environmental issues caused by extensive economic development.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that critical voices argue that the Green Deal could also be a potential non-tariff barrier to trade and could complicate further trade negotiations. In this respect, several studies highlight the potential impact of the Green Deal on international trade [50][51][52][53][54] and global dimensions (e.g., on the Global South) [50,[55][56][57][58][59]. A currently published US study [50] considered, on the basis of three scenarios, the impact of the strategies over a period of 8-10 years.…”
Section: Background: the European Green Deal And The European Farm To Fork Strategymentioning
confidence: 99%
“…Many countries have devised plans to cut GHG emissions. For instance, the European Commission plans to reduce GHG emissions by at least 55% compared to 1990 and become carbon neutral by 2050 [2].…”
Section: Introductionmentioning
confidence: 99%